Modern weapons and military equipment for issue 1/2014 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Unmanned air transport mules from Israel Sensor monitoring of land area Satellite telescope Moiraorbital weapons "cosmic dome" Automat for frogmen from Tula Heckler & Koch HK XM25, smart grenade launcher